Escalations risks in the Horn of Africa: Threats from Egypt, Ethiopia, and Somalia exacerbate local conflicts - Gerrit Kurtz; Stephan Roll; Tobiascvon Lossow (Stiftung Wissenschaft und Politik (SWP), 2024)
In recent months, relations between Ethiopia, Egypt, and Somalia have deteriorated significantly. Previously separate disputes have become intertwined: namely the conflict between Egypt and Ethiopia over the use of Nile waters and the disagreement between Ethiopia and Somalia regarding the recognition of Somaliland. The three countries use threats to improve their respective positions in these conflicts. While an interstate military escalation does not seem imminent at present, regional tensions are likely to rise, which could further empower the jihadist Al-Shabaab militia in Somalia. Germany and the European Union (EU) should recognise the highly complex interdependence of these lines of conflict, remind the countries concerned of their common interest in stabilising Somalia, and continue to advocate for dialogue in the Nile dispute. At the same time, it is also important to hold other influential actors more accountable to contribute to regional stability.
Keywords: 320; Horn of Africa; Ethiopia; Egypt; Somalia; Nile waters; recognition of Somaliland; jihadist Al-Shabaab militia; Abiy Ahmed; African Union (AU); Grand Ethiopian Renaissance Dam (GERD); Nile River Basin Commission (NRBC); Hassan Sheikh Mohamud; Ogaden National Liberation Front (ONLF)